La nature comme œuvre d’art: Élisée Reclus et les (néo)impressionnistes - Federico Ferretti (Belgeo)
This paper deals with the relationship that Élisée Reclus (1830-1905) and the circuit of Anarchist Geographers maintained with Art, which concerned at the same time their approach to Geography and their political engagement. Questioning Reclus’ texts on Art and drawing on primary sources on his networks, with the aid of international literature dealing with these topics, I address a relationship among Art, Geography and Politics in which the world was seen as an artwork, by the metaphor comparing the artist working on his materials for an esthetic aim to the engaged scientist working for bettering the world on a social and environmental standpoint, that is to say embellish it.